2002
DOI: 10.1191/0748233702th137oa
|View full text |Cite
|
Sign up to set email alerts
|

Concordance across species in the reproductive and developmental toxicity of tetrachloroethylene

Abstract: Reproductive and developmental toxicities resulting from exposure to tetrachloroethylene include delayed or impaired conception, sperm quality, death during development, developmental neurotoxicity, and growth retardation. In most cases there was concordance between rodents and humans. The risk assessments indicated that neurotoxicity was the most sensitive endpoint for inhalation, whereas growth retardation was the most sensitive endpoint when exposure was by the oral route. The reference concentration (RfC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The perinatal period, which encompasses the end of pregnancy and the early postnatal period, appears to be a susceptible window for exposure for perc across species (Beliles, 2002;Clewell et al, 2004) as estimates of perc in blood were higher during fetal exposure than during infancy . In addition, a few limited reports of adverse pregnancy outcomes during the first trimester of the pregnancy have also been observed Kyyrö nen et al, 1989;Taskinen et al, 1989).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The perinatal period, which encompasses the end of pregnancy and the early postnatal period, appears to be a susceptible window for exposure for perc across species (Beliles, 2002;Clewell et al, 2004) as estimates of perc in blood were higher during fetal exposure than during infancy . In addition, a few limited reports of adverse pregnancy outcomes during the first trimester of the pregnancy have also been observed Kyyrö nen et al, 1989;Taskinen et al, 1989).…”
Section: Discussionmentioning
confidence: 98%
“…Past reviews of the reproductive and developmental effects of perc exist (Beliles, 2002;Bove et al, 2002;Danielsson, 1990;Tabacova, 1986;van der Gulden and Zielhuis, 1989), but new data, particularly on developmental neurotoxicity and developmental immunotoxicity, are now available (Delfino et al, 2003b;Janulewicz et al, 2008;Lehmann et al, 2001;NYSDOH, 2005a-c;Schreiber et al, 2002;Windham et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…hormonal changes (100,187,216) menstrual irregularities c (187,188,193) decreased semen quality a (100, 188, 217, 218) reduced fertility b (188,(218)(219)(220)(221)(222) fetal loss d (187,188,193,223) miscarriage in female partner (188) Cigarette smoke Includes active and/or passive smoking hormonal changes (219, 224) IUGR (225) decreased semen quality a (219) Low birth weight (225) reduced fertility b (188,219) Preterm delivery (225) miscarriage (219) decreased semen quality a (124, 226) early menopause (219) hormonal changes (138-140, 187, 193, 236) altered estrous cycle (227) reduced fertility b (187,236) reduced fertility b (227) Organochlorine pesticides…”
Section: Air Pollutionmentioning
confidence: 99%
“…In fact, prolactin can be increased by exposure to lead (Govoni et al 1987;Lucchini et al 2000), organic mercury (Carta et al 2003), and manganese (Ellingsen et al 2003;Smargiassi and Mutti 1999;Takser et al 2004), but it can be decreased by exposure to inorganic mercury Lucchini et al 2003;Ramalingam et al 2003), alluminum (Alessio et al 1989), and cadmium (Calderoni et al 2005;). Subjects exposed to chemicals such as styrene (Bergamaschi et al 1996;Luderer et al 2004;Umemura et al 2005), perchloroethylene (Beliles 2002;Ferroni 1992), and anesthetic gases (Lucchini et al 1996;(Marana et al 2003) have shown an increase of serum prolactin, whereas polychlorinated biphenyls (De Krey et al 1994) Possible mechanisms, other than direct effects at the cellular level, may be related to different neurotransmitters involved in the modulation of prolactin secretion. For example, the dopaminergic and serotoninergic systems, respectively, are involved in the physiologic regulation of this hormone as a tonic inhibitor and as an excitatory modulator.…”
Section: Prolactin Changes As a Consequence Of Chemical Exposurementioning
confidence: 99%